Controls on formation and alteration of early diagenetic dolomite: A multi-proxy δ44/40Ca, δ26Mg, δ18O and δ13C approach. (15th August 2020) - Riechelmann, Sylvia; Mavromatis, Vasileios; Buhl, Dieter; Dietzel, Martin; Immenhauser, Adrian
Abstract: The full potential of the dolomite Ca isotope proxy only unfolds when combined with data of the other main elements (C, O, Mg) in the crystal lattice of Mg-carbonates. Data presented here reveal the level of complexity inherent to dolomite precipitation and alteration environments and add new constraints to the understanding of early diagenetic dolomite formation. Well-constrained Precambrian to Pleistocene dolomites were investigated, representing three characteristic formation and alteration environments: (i) sabkha, (ii) altered marine and (iii) lacustrine/palustrine dolomites. Primary sabkha dolomites with typically low cation ordering degree (COD), high δ 13 C and low δ 44/40 Ca values contrast with recrystallized sabkha dolomites with relatively high COD, low δ 13 C and high δ 44/40 Ca values. Both δ 13 C and δ 44/40 Ca values of sabkha dolomite bear witness to the relative effects of kinetic and equilibrium Ca isotope fractionation conditions. Primary sabkha dolomites display Δ 44/40 Cadolomite-fluid ranging from −0.4 to −1.3‰, whereas recrystallized dolomite is approaching isotopic equilibrium (Δ 44/40 Cadolomite-fluid ∼ 0‰). Using the fractionation factor deduced from the sabkha dolomite data set, recrystallized Precambrian dolomite points to a δ 44/40 Caseawater/pore fluid of about 1.2‰ (SRM 915a), a value that is distinctively lower compared to previously suggested ones and modern seawater. Altered marine dolomites display evidence for meteoric overprint, indicated by δ 18 O values as low as −4.62‰. Both Mg and Ca isotope signatures correlate with δ 18 O values of altered marine dolomites, whereas δ 13 C values lack correlation with the other isotope systems. We propose that freshwater circulated through silicate aquifers prior to reaching the dolostone units and Ca, Mg and O isotopes of altered marine dolomites reflect variable degrees of this meteoric overprint. Lacustrine/palustrine dolomites display a correlation between the isotope values of C, Mg and Ca. These dolomites are formed during pulses of marine ingression in swamp, playa and lake environments and are thus characterized by water-logged conditions (anaerobic) and saline, sulfate-rich fluids. Bacterial-sulfate reduction induces dolomite formation and leads to lower δ 13 C and δ 44/40 Ca as well as to higher δ 26 Mg values. The Ca isotope proxy acts as a benchmark against which other proxy data can be calibrated or processes tested. Taking COD and dolomite stoichiometry into consideration, the here documented multi-proxy isotope approach is promising and provides benchmarks against which proxy signals can be calibrated and tested. Interestingly, even the limited data sets shown here point to patterns that can be interpreted in a meaningful manner that is of relevance for dolomite research.